Creating the competitive edge: A new relationship between operations management and industrial policy. Issue 1 (1st February 2017) - Spring, Martin; Hughes, Alan; Mason, Katy; McCaffrey, Paul
Abstract: Policy interventions by governments to alter the structure of economic activity have either been dismissed or ignored by operations management (OM) scholars. However, in recent years, such 'industrial policy' measures have gained increasing support in developed economies, particularly in relation to manufacturing. This paper argues that contemporary manufacturing in high‐cost economies is rooted in technological innovation. As such, it can be enhanced by industrial policy interventions that prevent systems failures in the process of turning technological innovation into commercially viable products. In particular, we argue that this can be achieved by establishing non‐firm, intermediate research organizations and by other measures to change the institutional architecture of an economy. We disagree with claims in earlier OM literature that industrial policy is all but irrelevant to manufacturing firms and to OM. Instead, we argue that OM must broaden its conceptual scope so as to encompass active engagement with non‐firm network participants such as government‐supported intermediate research organizations, and that, as well as learning to be effective users of industrial policy, OM practitioners and academics should engage actively in the development of industrial policy. In this way, high‐value, high‐productivity manufacturing can be viable in high‐cost economic environments.